Peran Serta Masyarakat Terhadap Rehabilitasi Hutan dan Lahan di Kota Palopo - Indhasari, Fitri; Kuddus, Abdul (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2021)
The condition of forest and land damage is a concern for many parties, one of the government’s efforts is through forest and land rehabilitation activities. Forest and land rehabilitation activities are not only the government’s business, but all communities, especially those directly involved in the exploitation of land resources are expected to be able to overcome the problem of land damage. The aim of this research was to determine forest and land rehabilitation activities and community participation in land rehabilitation activities. This research was conducted from April to June 2021. The method used in this research was the descriptive method with observations, direct interviews and taking documentation of activities. The results showed that community participation in forest and land rehabilitation activities had positive and negative roles by forming farmer groups that played an active role by holding consultations with the government in preserving forests.